2023
DOI: 10.1021/acsapm.3c01585
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Structure and Thermal Properties of Energetic Binders for Application in Propulsion

Ling Chen,
Binbin Wang,
Jianwei Zhang
et al.

Abstract: Energetic binders, essential components of energetic materials (EMs), act as the main support for the energy and mechanical properties of propulsion. Compared with conventional nitrocellulose (NC), the two binders, nitrated bacterial cellulose (NBC) and nitrate glycerol ether cellulose (NGEC), exhibit promising applications in enhancing the mechanical strength of propulsion due to their inherent physicochemical features. Herein, we present a series of characterizations and methods to study the structures of NC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…It can be inferred that the high-pressure condition could produce a catalytic effect on the thermal decomposition process of the propellant, while the T p of the propellant with a low content of GNSs under low pressure (0–3 MPa) exhibited slight variation while exerting reduced or increased fluctuation when the pressure reached 5 MPa. It means that the products of thermal decomposition mainly promote the heat release of the propellant instead of T p under high-pressure conditions . Besides, it can also be found that the T p of the propellant with a low content of GNSs exerted an increase under low pressure for 0–3 MPa and presented a decrease when that reached 5 MPa.…”
Section: Results and Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…It can be inferred that the high-pressure condition could produce a catalytic effect on the thermal decomposition process of the propellant, while the T p of the propellant with a low content of GNSs under low pressure (0–3 MPa) exhibited slight variation while exerting reduced or increased fluctuation when the pressure reached 5 MPa. It means that the products of thermal decomposition mainly promote the heat release of the propellant instead of T p under high-pressure conditions . Besides, it can also be found that the T p of the propellant with a low content of GNSs exerted an increase under low pressure for 0–3 MPa and presented a decrease when that reached 5 MPa.…”
Section: Results and Discussionmentioning
confidence: 90%
“…It means that the products of thermal decomposition mainly promote the heat release of the propellant instead of T p under high-pressure conditions. 39 Besides, it can also be found that the T p of the propellant with a low content of GNSs exerted an increase under low pressure for 0−3 MPa and presented a decrease when that reached 5…”
Section: Thermal Decomposition Characteristic Under High Pressurementioning
confidence: 93%
“…11). It is observed that there is only one exothermic peak, corresponding to the thermal decomposition reaction peak of the NC/NG system, 21,22 wherein the decomposition peak temperature ( T p ) is about 200 °C. It can be found that the thermal decomposition temperature increases slightly with the increase in relative humidity, which may be due to the fact that the density of the dry propellant at 80% RH is smaller, and the pores are occupied by air, which is unfavorable for heat transfer.…”
Section: Resultsmentioning
confidence: 99%